SELF-PROCESSES AS A RESOURCE OF TEACHER'S PERSONAL AND PROFESSIONAL DEVELOPMENT (Education in the 21st Century, 2023)
The article is devoted to the problem of the teachers development as a person and a professional. The psychological and pedagogical literature on this problem was studied, the essence of personal and professional development was determined. The scientific search for resources that provide this process is carried out, attention is focused on the human «self» – a set of self-processes and self-abilities.The following self-processes are considered as priorities: self-knowledge, self-analysis, self-reflection, self-organization, self-projection, self-development, self-improvement. According to the author of the article, they are those which significantly influence on the quality of the specialist's personal and professional development.The results of self-process research by foreign and national scientists are analyzed. On the basis of the studied results, conclusions are made that self-processes play the role of an internal resource, thanks to which the personal and professional sphere of the teacher develops more intensively.